Pengaruh Perkembangan Kegiatan Perdagangan dan Jasa terhadap Perubahan Penggunaan Lahan di Kawasan Solo Baru - Dina Arifia; Soedwiwahjono Soedwiwahjono; Rizon Pamardhi Utomo (Universitas Sebelas Maret Surakarta, 2017)
Solo Baru region has a very strategic location and were originally intended for residential areas, but then experienced a rapid development of economic activities. The development of economic activity is the most visible trade activities and services that continue to increase precisely since 2002. The development of trade and services activities is of course have an influence on land use changes that occur rapidly in Solo Baru region. Based on these issues, the formulation of the problem in this research is how the influence brought about by the development of the activity of trade in services to changes in land use. In line with these problems, this study aims to determine the effect of the development of trading activities and services to changes in land use Solo Baru Region. The method used is quantitative descriptive to determine the level of development to later described spatially. These results indicate that the development of trade and services activities has encouraged the development of other activities either similar activities (commercial) as well as supporting activities (housing, public services, and industry) so the impact on the provision of land. The need for this land that drives the changes in land use, both in terms of area, intensity, and land use patterns are formed. Developments are vertically making it more influential in the development of land compared to the intensity of the land area. Besides land development patterns that are formed are random pattern of development as the region woke formed does not have a specific shape (sporadic) and develop segmental. Keywords: Activities Development, Trade and Services Activity, Land Use Change